Philosophy and reality - Salazar Paniagua, Freddy (Estudios de Filosofía, 1994)
Accounting for reality is a task that justifies the very existence of philosophy. Philosophy arises out of its origins in the decline of myth and finds its corroboration in the course of its history. However, this history also reveals to what extent that essential task has been forgotten, reducing philosophy to the activity of practicing an exegesis of texts that have no relation to historical happening. Based on this theoretical model, philosophical activity in Colombia is criticized and suggestions are made, with an aim set on correcting certain errors that occur in the teaching of philosophy.